Naphthofluorescein-based organic nanoparticles with superior stability for near-infrared photothermal therapy. Issue 28 (6th July 2022) - An, Jing; Tang, Shanliang; Feng, Erting; Tian, Mingyu; Chen, Wenlong; Chen, Miaomiao; Hong, Gaobo; Peng, Xiaojun; Song, Fengling
Abstract : Photothermal agents (PTAs) based on organic small molecules with near-infrared (NIR) absorption (700–900 nm) have attracted increasing attention in cancer photothermal therapy (PTT). Abstract : Photothermal agents (PTAs) based on organic small molecules with near-infrared (NIR) absorption (700–900 nm) have attracted increasing attention in cancer photothermal therapy (PTT). However, NIR organic PTAs often suffer from poor stability. Fluorescein and its derivatives have been widely used in biological imaging and sensing due to their minimal cytotoxicity. But fluorescein and its derivatives have not been used in PTT because most of them don't have NIR absorption. In this work, two NIR naphthofluorescein derivatives, namely NFOM-1 and NFOM-2, were synthesized. In contrast to NFOM-1, NFOM-2 possesses an intramolecular hydrogen bonding network, which extends the absorption to the NIR region and significantly improves the photostability. NFOM-2 was encapsulated into an amphiphilic polymer (DSPE-mPEG2000) to obtain NFOMNPs as PTAs. Compared to the organic molecule NFOM-2, the absorption of NFOMNPs is broadened and further red-shifted to fit an 808 nm light source. Moreover, NFOMNPs exhibit good photothermal conversion efficiency (PCE, 40.4%, 808 nm, 1.0 W cm −2 ), remarkable photostability and physiological stability, and significant PTT efficacy in vitro and in vivo was achieved. In other words, this study provides an intramolecular hydrogen bond network strategy and a fluorescein-based molecular platform to construct ultra-stable PTAs for efficient NIR PTT.